More production, less erosion: a Kenyan case history - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Erosion is one of the most common causes of declining soil fertility and productivity in ACP countries and farmers often avoid anti-erosion measures because of the labour required. One exception is the successful soil and water conservation...